Praktik Au Pair di Tiongkok melalui Jalur Mandiri (Non-Agen): Studi Autoetnografi tentang Mobilitas Global Informal - Mahdalia, Errica (VISA: Journal of Vision and Ideas, 2026)
This study aims to examine the practice of au pairing in China through non-agency channels as a form of global mobility developing outside of formal mechanisms. This study uses a qualitative approach with autoethnography methods, where the author's experience as an au pair serves as the primary data source to understand the process, relationship dynamics, and challenges faced during the program. The results show that the process of becoming an au pair through non-agency channels is carried out independently through the use of digital networks, such as host family search platforms and social media. The selection process and employment agreement take place directly between the prospective au pair and the host family through informal communication. In practice, aspects such as work duration, pocket money, and accommodation facilities are part of the agreement, which is negotiated personally. This study also found that various challenges arise, including language differences and cultural differences, as well as the process of adapting to a new environment. Furthermore, legal aspects are a concern due to the lack of specific regulations regarding the au pair program in China. In these conditions, individuals are required to have adaptability and initiative in managing various needs during the program. The relationship between the au pair and the host family is dynamic, with role negotiations occurring in daily interactions. In the absence of institutional support, au pairs develop protective mechanisms through social networks and preventative strategies to maintain safety and comfort during their stay in the destination country. Overall, this study provides an overview of the practices of non-agency au pairs and demonstrates how individuals navigate informal global mobility independently.